2018
DOI: 10.1051/epjconf/201817007014
|View full text |Cite
|
Sign up to set email alerts
|

Remote inspection with multi-copters, radiological sensors and SLAM techniques

Abstract: Abstract-Activated material can be found in different scenarios, such as in nuclear reactor facilities or medical facilities (e.g. in positron emission tomography commonly known as PET scanning). In addition, there are unexpected scenarios resulting from possible accidents, or where dangerous material is hidden for terrorism attacks using nuclear weapons. Thus, a technological solution is important to cope with fast and reliable remote inspection. The multi-copter is a common type of Unmanned Aerial Vehicle (U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 10 publications
(12 reference statements)
0
6
0
Order By: Relevance
“…where f denotes the focal length of the camera, d denotes the actual size of the target, and D denotes the pixel size of the target in the image. Therefore, the angle measurement error range is described by equation ( 14) based on equations ( 12) and (13).…”
Section: Image Preprocessingmentioning
confidence: 99%
See 1 more Smart Citation
“…where f denotes the focal length of the camera, d denotes the actual size of the target, and D denotes the pixel size of the target in the image. Therefore, the angle measurement error range is described by equation ( 14) based on equations ( 12) and (13).…”
Section: Image Preprocessingmentioning
confidence: 99%
“…It can be found that a single sensor is usually used for a specific detection or a certain stage of general detection because of incomplete detection information or low measurement accuracy. To overcome the limitations of single sensor detection, multi-sensor information fusion (MSIF) systems have been widely used in many fields, such as fault detection [7], remote sensing [8], systems monitoring [9], robot systems [10], human-computer interaction [11], control systems [12], and target recognition [13]. The MSIF systems can detect obstacles in multiple dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…Promising results were obtained in an indoor scenario using weak sources. However, some limitations are expected when using UAV for the inspection of fusion reactors (indoor), namely the high temperature and the high dose rates [ 147 ]. This concept is also valid for other scenarios, like the inspection of contaminated areas in fission reactors (e.g., leakage detection), storage areas (nuclear sources), or reactor accidents.…”
Section: Mobile Radiation Detection Systemsmentioning
confidence: 99%
“…Multi-source and heterogeneous information fusion (MSHIF) makes integrated utilization of the information obtained by different sensors, which avoids the perceptual limitations and uncertainties of a single sensor, forms a more comprehensive perception and recognition of the environment or target, and improves the external perception ability of the system [1]. At present, MSHIF technology has been comprehensively applied in such fields as fault detection [2], [3], remote sensing [4], human health monitoring [5], [6], robot system [7], human-machine interaction [8], target recognition and tracking [9], [10], simultaneous localization and mapping (SLAM) [11] and advanced driver assistance system (ADAS) [12]. Automated driving (AD) is not a single technology, but a highly complicated system composed of many subsystems, which contains three parts:…”
Section: Introductionmentioning
confidence: 99%